2000
DOI: 10.1093/rheumatology/39.8.894
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy of radon spa therapy in rheumatoid arthritis—a randomized, sham‐controlled study and follow‐up

Abstract: Marked short-term improvements in both groups at the end of treatment may have masked potential specific therapeutic effects of radon baths. However, after 6 months of follow-up the effects were lasting only in patients of the radon arm. This suggests that this component of the rehabilitative intervention can induce beneficial long-term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0
15

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 23 publications
4
102
0
15
Order By: Relevance
“…The present study showed that antioxidative functions were significantly higher in mice that had inhaled radon at a concentration of 2000 Bq/m 3 for 24 hr than in control mice. Most conditions treated with radon therapy are pain-related diseases such as osteoarthritis [15] and rheumatoid arthritis [24]. Another research group reported that radon inhalation significantly increased β-endorphin and M-enkephalin which both have morphine-like analgesic effects [25].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that antioxidative functions were significantly higher in mice that had inhaled radon at a concentration of 2000 Bq/m 3 for 24 hr than in control mice. Most conditions treated with radon therapy are pain-related diseases such as osteoarthritis [15] and rheumatoid arthritis [24]. Another research group reported that radon inhalation significantly increased β-endorphin and M-enkephalin which both have morphine-like analgesic effects [25].…”
Section: Discussionmentioning
confidence: 99%
“…In Jáchymov, Czech Republic, the worldfamous radium spa is operating four water springs with maximal radon content of 5-20 kBq/L [73]. Despite of insufficient number of clinical trials [74] and some controversies in the radon therapies [75,76], the long-term experience demonstrably confirms the benefits for the patients and justifies its use, further confirmed by many independent scientific studies [77][78][79][80]. The spa medical praxis was verified by decades and is supported also by other epidemiologic studies on the hormesis theory that supports the beneficial effects of low-dose radon exposure [81][82][83].…”
Section: Applications and Use Of Radonmentioning
confidence: 99%
“…Most of the current results of radon balneology have been published in German (e.g. [59]), with only recently some papers also appearing in English [61,63]. Of particular interest in the Morbus Bechterew therapy are studies about the combination of radon therapy and exercise treatment [64], which clearly show the superiority of the added radon treatment, with the longer lasting effect clearly compensating the higher cost of such a combination.…”
Section: Radon Therapy Of Degenerative Diseases Of Joints and Spine Imentioning
confidence: 99%